Pembuatan Web Unit Produksi Coffee Santri di Aziz Paradise - Dina Merlinda Izzah; maulana , hapid (Jurnal Teknologi dan Bisnis, 2021)
Along with the development of technology, the need for information can trigger services that are easier, faster and more practical, especially in doing business. Entrepreneurs today are competing with each other to innovate, almost all businesses, both medium and small businesses use technology to increase promotion of places and products. To attract buyers, an attractive website appearance is needed so that it can increase the attractiveness of buyers. In this study, we propose an attractive website display design using the Laravel framework and with a drink menu recommendation feature based on certain diseases and based on mood with the KNN Algorithm with the prototype method. To ensure that the website can be accepted by users, a system assessment is carried out from a user point of view using User Acceptance Testing (UAT). It was found that the system received an "Agree" rating after the UAT average score, meaning that the web-based application of the Coffee Santri Production Unit in Aziz Paradise succeeded in meeting the system standards desired by the user.